The Financial Accelerator and the real economy. Self-reinforcing feedback loops in a core macro econometric model for Norway - Roger Hammersland; Cathrine Bolstad Træe (Statistics Norway, Research Department, 2011)
This paper gives a brief description and studies the salient features of a core macro-econometric model that allows for self-reinforcing co-movements between credit, asset prices and real economic activity, often denominated a financial accelerator in the literature. In contrast to the economic literature that cultivates highly stylized model representations aimed at illustrating the working and the implications of such a feature, the model of this paper integrates no less than two mutually reinforcing financial accelerator mechanisms in a full-fledged core macroeconomic model framework. Noteworthy, the impulse response pattern overall of such a model turns out to be very much in line with the ones one would have expected using a SVAR/DSGE modelling framework, though the amplitude of shocks is in most cases stronger than the ones pertaining to these kind of models. This is due to the working of the financial accelerators that contribute to magnify the effects of shocks to the economy. Furthermore, a forecast comparison undertaken between our model and an alternative macro econometric model not furnished with a financial block, suggests that financial feedback mechanisms have got the potential of boosting the forecasting property of theory-informed macro econometric models. Hence, in addition to enhancing the practical relevance of a model by incorporating a mechanism of high real-world authenticity, financial accelerators seem to come with a couple of values added. Namely, to i) guarantee against a systematic underestimation of the effects of macroeconomic shocks and to ii) be forecast-promoting
Keywords: E1; E32; E44; 330; The Financial Accelerator; Structural Vector Error Correction Modelling; Core Macroeconomic Modelling; Impulse response analysis